Dissipative soliton generation in Er-doped fibre laser using SnS2 as a saturable absorber. (10th September 2019) - Li, Shi; Yin, Yu; Ouyang, Qiuyun; Chen, Yujin; Lewis, Elfed; Farrell, Gerald; Tokurakawa, Masaki; Harun, Sulaiman Wadi; Wang, Pengfei
Abstract: Dissipative soliton generation is successfully demonstrated in an Erbium-doped mode-locked fibre laser using Tin Disulfide (SnS2 ) as a saturable absorber in the near-zero dispersion regime. A stable dissipative soliton pulse train operating at a wavelength of 1560 nm is successfully obtained with a 32 nm FWHM power. The 152 fs pulses were produced using 0.48 nJ of pulse energy in the all-fibre laser cavity following compression in a single-mode fibre.